From pluralism to tolerance: The role of project-based social studies learning in Islamic schools - Nur Chamidah; Ali Nasith; Alfiyana Yuli Efiyanti (Harmoni Sosial: Jurnal Pendidikan IPS, 2026)
This study uses a mixed method with a sequential exploratory model approach. The research population consisted of 120 students with a sample of 92 eighth-grade students at MTsN 1 Kediri City. Qualitative data were obtained from interviews, observations, and documentation. Meanwhile, quantitative data were obtained through the distribution of questionnaires using a Likert scale (Cronbach's Alpha > 0.97). The results showed that pluralism had been systematically integrated into teaching modules through heterogeneous group discussions and problem-based learning. This application was reinforced by the P5RA (Rahmatan Lil Alamin Student Profile Strengthening Project) school program, which is a character-building program for students in instilling Islamic values and understanding cross-cultural diversity.  Simple linear regression analysis produced a p-value of 0.000 < 0.05, indicating that the integration of pluralism values in Social Studies (IPS) learning has an effect on students' tolerance levels in Islamic-based educational institutions. Thus, the application of pluralism values in IPS learning, implemented through heterogeneous project-based learning and school programs in the form of cultural performances, has been proven to be effective in increasing student tolerance.